PENGARUH MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN TEKNIK DASAR SERVIS PENDEK DALAM PEMBELAJARAN BULUTANGKIS SISWA KELAS VIII SMPN 2 TELUKJAMBE BARAT - Sri Rahayu; Sutirna; Setio Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine, analyze, and identify the influence of audio-visual media on basic short serve skills in badminton instruction at SMP Negeri 2 Telukjambe Barat. The study employed a quantitative approach using a pre-experimental design with a One Group Pretest Posttest Design. The population in this study consisted of 337 eighth-grade students, with a sample of 41 students selected using cluster random sampling. The instrument used was a short serve skill test in badminton. The results of this study showed significant results, as evidenced by the pretest average score of 50.80, which increased to 68.37 after the treatment and posttest. Additionally, the results of the paired sample t-test calculation yielded a significance value of 0.000 (sig. (2-tailed) < 0.05), indicating a significant effect on short serve skills between the pretest and posttest data. This means that there is a significant effect from the treatment that was administered. This effect is demonstrated by the increased influence of audio-visual media on basic short serve skills in badminton learning activities for eighth-grade students at SMP Negeri 2 Telukjambe Barat.